Is working in later life good for your health? A systematic review of health outcomes resulting from extended working lives - Susan Baxter; Lindsay Blank; Anna Cantrell; Elizabeth Goyder (BMC, 2021)
Abstract Background Work, rather than unemployment, is recognised as being good for health, but there may be an age when the benefits are outweighed by adverse impacts. As countries around the world increase their typical retirement age, the potential effect on population health and health inequalities requires scrutiny. Methods We carried out a systematic review of literature published since 2011 from developed countries on the health effects of employment in those over 64 years of age. We completed a narrative synthesis and used harvest plots to map the direction and volume of evidence for the outcomes reported. We followed the Preferred Reporting Items for Systematic Reviews (PRISMA) checklist in our methods and reporting. Results We identified seventeen relevant studies, which were of cohort or cross-sectional design. The results indicate evidence of beneficial or neutral effects from extended working on overall health status and physical health for many employees, and mixed effects on mental health. The benefits reported however, are most likely to be for males, those working part-time or reducing to part-time, and employees in jobs which are not low quality or low reward. Conclusions Extending working life (particularly part time) may have benefits or a neutral effect for some, but adverse effects for others in high demand or low reward jobs. There is the potential for widening health inequalities between those who can choose to reduce their working hours, and those who need to continue working full time for financial reasons. There is a lack of evidence for effects on quality of life, and a dearth of interventions enabling older workers to extend their healthy working life.